Socio economi characteristics as determinants of cattle farmer information exposured (A Case Study in Sundamekar, Sumedang) - I A Trijaya; R W E Lumintang; D U Wardhani (Media Peternakan, 2001)
Socio economi characteristics as determinants of cattle farmer information exposured (A Case Study in Sundamekar, Sumedang)